2024
DOI: 10.1002/2211-5463.13780
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid alleviates obesity‐induced skeletal muscle atrophy via the PI3K/Akt signaling pathway

Yaqin Sun,
Xiaofang Wei,
Tong Zhao
et al.

Abstract: Oleanolic acid (OA) is a pentacyclic triterpene with reported protective effects against various diseases, including diabetes, hepatitis, and different cancers. However, the effects of OA on obesity‐induced muscle atrophy remain largely unknown. This study investigated the effects of OA on skeletal muscle production and proliferation of C2C12 cells. We report that OA significantly increased skeletal muscle mass and improved glucose intolerance and insulin resistance. OA inhibited dexamethasone (Dex)‐induced mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…It was found that OA significantly boosts skeletal muscle mass, improves glucose intolerance and insulin resistance, and inhibits dexamethasone-induced muscle atrophy by regulating the PI3K/Akt pathway. Moreover, OA reduces the expression of atrophy-related genes in the skeletal muscle of obese mice and enhances PI3K/Akt activation, promoting protein synthesis and alleviating muscle atrophy [ 75 ]. A study investigated OA’s therapeutic effects on renal ischemia reperfusion injury (RIRI) and its mechanism.…”
Section: Pharmacological Activities Of Oamentioning
confidence: 99%
“…It was found that OA significantly boosts skeletal muscle mass, improves glucose intolerance and insulin resistance, and inhibits dexamethasone-induced muscle atrophy by regulating the PI3K/Akt pathway. Moreover, OA reduces the expression of atrophy-related genes in the skeletal muscle of obese mice and enhances PI3K/Akt activation, promoting protein synthesis and alleviating muscle atrophy [ 75 ]. A study investigated OA’s therapeutic effects on renal ischemia reperfusion injury (RIRI) and its mechanism.…”
Section: Pharmacological Activities Of Oamentioning
confidence: 99%